Экзотизмы как особенная категория заимствований - Kozyra, Marzena (Acta Polono-Ruthenica, 2019)
This article is aimed at establishing the place of exoticisms against the spectrum of other loan words. We consider increased language and cultural contacts, intensified in recent years. Additionally, we focus on the typology of loan words, taking into account their degree of assimilation to the rules of the recipient language. We define exoticisms as unassimilated loan words, whose main aim is to re-create various national features and name unknown cultural phenomena. The domination of cultural traits in the semantic structure of exoticisms (which constitutes the hallmark of this lexical group) is the basis of the proposed relation between the analyzed loan words and the so-called words-realities. Moreover, we put stress on the particular spheres of life in which exoticisms are used, as well as on their inner differentiation, connected with the nativization processes affecting the language.